Effects of prenatal nutrient supplementation and early life exposures on neurodevelopment at age 10: a randomised controlled trial - the COPSYCH study protocol. Issue 2 (1st February 2022) - Mohammadzadeh, Parisa; Rosenberg, Julie Bøjstrup; Vinding, Rebecca; Møllegaard Jepsen, Jens Richardt; Lindberg, Ulrich; Følsgaard, Nilo; Erlang Sørensen, Mikkel; Sulaiman, Daban; Bilenberg, Niels; Mitta Raghava, Jayachandra; Fagerlund, Birgitte; Vestergaard, Mark; et al.
Abstract : Introduction: Nutrient deficiency and immune and inflammatory disturbances in early life may compromise neurodevelopment and be implicated in the aetiology of psychiatric disorders. However, current evidence is limited by its predominantly observational nature. COpenhagen Prospective Study on Neuro-PSYCHiatric Development (COPSYCH) is a research alliance between Copenhagen Prospective Studies on Asthma in Childhood (COPSAC) and Center for Clinical Intervention and Neuropsychiatric Schizophrenia Research with the overall aim to investigate effects of prenatal and early life exposures on neurodevelopment at 10 years. COPSYCH will investigate the impact of prenatal n-3 long-chain polyunsaturated fatty acids (n-3 LCPUFA) and high-dose vitamin D supplementation on neurodevelopment reflected by brain development, neurocognition and psychopathology. Moreover, the neurodevelopmental impact of early life exposures such as infections, low grade inflammation and the gut microbiome will be scrutinised. Methods and analysis: COPSYCH is based on the prospective and ongoing COPSAC2010 birth cohort of 700 mother–child pairs. Randomised controlled trials of supplementation with n-3 LCPUFA and/or high-dose vitamin D or placebo in the third trimester were embedded in a factorial 2×2 design (ClinicalTrials.gov: NCT01233297 and NCT00856947 ). This unique cohort provides deep phenotyping data from 14 previous clinical follow-up visits and exposure assessments since birth. The ongoing 10-year visit is a 2-day visit. Day 1 includes a comprehensive neurocognitive examination, and assessment of psychopathological dimensions, and assessment of categorical psychopathology. Day 2 includes acquisition of brain structural, diffusion and functional sequences using 3 Tesla MRI. Study outcomes are neurocognitive, psychopathological and MRI measures. Ethics and dissemination: This study has been approved by the Danish National Committee on Health Research Ethics and The Danish Data Protection Agency. The study is conducted in accordance with the guiding principles of the Declaration of Helsinki. Parents gave written informed consent before enrolment.